Inserção da região centro ocidental no cenário econômico do Paraná : atividades industriais - Borges, Paulo Roberto Santana (2015)
This thesis aims to analyze the current insertion of Campo Mourão and the Western Central Mesoregion regarding the economic scenario of Paraná with emphasis on industrial activities. We have started our research on the industries of Paraná, concerning the State's industrial profile and spatiality of investments and approaching the State's industrial trajectory, considering the capital restructuring, especially the industrial deconcentration and what implications that has brought to Paraná in its several regions . At a later time we have referred specifically to the Western Central Mesoregion ant its industry major sectors with discussions regarding production, employment, investments among other economic and social variables comparing the ten geographic mesoregions of Paraná. Next, we have approached the industries of the cities in the Western Central region with emphasis on the main industrial facilities with a wide consideration of data as a way to show the dynamics, profile and the relevance of the industrial sector. We have used national and international theoretical framework within the range of Geography and Economics, among other sciences when necessary; We have collected secondary data through main Research Institutes in Brazil, as well as primary information through interviews with City Halls representatives, commercial and industrial associations and major industries in the region. At the end of the study the research revealed the importance of the industry to the local environment and region and demonstrated the economic insertion of this sector in the State of Paraná, as evidenced by prominent companies in the domestic and international market.